Transcriptome Analyses of Staphylococcus aureus Grown in Platelet Concentrates with Focus on Virulence - Paredes, Carina (Université d'Ottawa | University of Ottawa, 2026)
Platelet concentrates (PCs), used to treat bleeding disorders, are stored at 22 ± 2°C under agitation to maintain platelet function; however, these conditions favor growth of bacteria introduced during venipuncture. Staphylococcus aureus is a predominant PC contaminant and has been involved in septic transfusion reactions. The Ramirez’ lab has demonstrated that PC storage elicits differential regulation of bacterial virulence genes. I therefore hypothesized that the PC storage environment triggers transcriptional changes in S. aureus resulting in enhanced antibiotic resistance. Furthermore, these transcriptional changes result in enhanced virulence of S. aureus grown in PCs. These hypotheses were tested with two objectives: (1) assess differential expression of antibiotic resistance genes in S. aureus grown in PCs compared to tryptic soy broth (TSB), and (2) study the role of the NorB efflux pump on the virulence of S. aureus grown in PCs. Four transfusion relevant S. aureus strains (TRS) were grown in PCs and TSB and subjected to comparative transcriptome analyses. These studies revealed that the norB gene (encodes for the efflux pump NorB, which is implicated in quinolone resistance and negatively regulated by MgrA) was upregulated in PC-grown TRS compared to TSB cultures. Furthermore, Minimal Bactericidal Concentration (MBC) assays showed increased quinolone resistance in PC cultures of TRS versus TSB cultures. MBC and RT-qPCR assays with non-transfusion relevant strains (S. aureus RN6390, RN6390ΔnorB, and RN6390ΔmgrA) indicated that not only NorB, but also efflux pumps NorA and NorC, may be involved in enhanced quinolone resistance in PC-grown S. aureus. The impact of the PC storage environment on regulation of quinolone resistance driven by Nor efflux pumps has not been reported before. Furthermore, NorB was shown to be implicated in S. aureus virulence using a silkworm model. The use of silkworm larvae to evaluate virulence of S. aureus driven by NorB is novel and inform the research and transfusion medical communities about potential targets to minimize the risk of transfusing contaminated blood products. My research has open venues for further investigation on the role of efflux pumps in quinolone resistance and virulence in S. aureus grown in PCs, which could be used to propose mechanisms to enhance the safety of transfusion patients.
Keywords: Platelet concentrates; Staphylococcus aureus; Virulence; Antibiotic resitance; Efflux pumps; Quinolones